Pertumbuhan Ekonomi di Negara-negara Muslim Asia Tenggara Menurut Perspektif Ekonomi Islam (Studi Kasus Indonesia dan Malaysia) - Badrun Nisa; M. Ridwan; Maryam Batubara (ITB AAS INDONESIA Surakarta, 2023)
This study aims to identify and analyze economic growth in Southeast Asian Muslim countries from an Islamic economic perspective (case studies of Indonesia and Malaysia). This type of research is causal associative. The population for this study is Indonesia and Malaysia. The population in this study is all data on the development of foreign investment, exports, inflation and exchange rates and GDP data in Indonesia and Malaysia in 2006-2021. so that the number of samples used is 32 sample data. Methods of data analysis using multiple linear regression. The results showed that exports and inflation had a partial effect on profit growth, while foreign investment and exchange rates had no effect on economic growth in Indonesia and Malaysia. Foreign Investment, Exports, inflation and exchange rates simultaneously influence Economic Growth in Indonesia and Malaysia from an Islamic perspective. From the analysis of the Islamic economic perspective, it can be concluded that in order to realize economic growth for the community, the objectives and facilities used must be in accordance with sharia values and principles based on the Al Quran and Sunnah. Islamic expenditure theory uses principles taken from Al-Qawaid Al-Fiqhiyyah in order to avoid potential spending inefficiencies, as well as Islamic consumption norms.